2019
DOI: 10.1172/jci121955
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid–induced YAP/TAZ activation promotes developmental angiogenesis by repressing Notch ligand Dll4

Abstract: al cooperation between LPA4 and LPA6 is essential for embryonic development. Since Lpa4;Lpa5-DKO and Lpa5;Lpa6-DKO mice were born at the expected Mendelian ratios and had no obvious abnormalities (Supplemental Tables 4 and 5), LPA5 is unlikely to be involved in embryonic development. To examine the roles of LPA4 and LPA6 in embryonic development, yolk sac and embryo proper were observed at various stages of gestation. At E8.5, both Lpa4;Lpa6-DKO yolk sac and embryo proper appeared normal (Supplemental Figure 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 77 publications
3
77
0
Order By: Relevance
“…Tumor microenvironments are very heterogeneous and cancer type-specific, implying that ATX/LPA signaling outcome will critically depend on the composition and LPAR expression repertoire of the immune cell infiltrate. LPAR6 is of special interest here as it provides a crucial link with ATX and G13 during embryonic development (van Meeteren et al, 2006;Yasuda et al, 2019) and is abundantly expressed in immune cells ( Figure 3D). LPAR6 has a rather low affinity for 1-acyl-LPA species (Yung et al, 2014), which may explain the relatively high IC50 value for 1-oleyl-LPA observed in the T-cell migration assays (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor microenvironments are very heterogeneous and cancer type-specific, implying that ATX/LPA signaling outcome will critically depend on the composition and LPAR expression repertoire of the immune cell infiltrate. LPAR6 is of special interest here as it provides a crucial link with ATX and G13 during embryonic development (van Meeteren et al, 2006;Yasuda et al, 2019) and is abundantly expressed in immune cells ( Figure 3D). LPAR6 has a rather low affinity for 1-acyl-LPA species (Yung et al, 2014), which may explain the relatively high IC50 value for 1-oleyl-LPA observed in the T-cell migration assays (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In our studies, we observed a strong upregulation of YAP/TAZ target genes Cyr61 and Ctgf due to loading; this response was significantly abrogated by YAP/TAZ inhibitor VP only under the delayed loading condition. These results suggest that delayed loading activates YAP signaling (perhaps through Itgb1), which leads to an increased number of active sprout tip cells (53) and thus upregulation of genes associated with active tip cells, to enhance vascularization.…”
Section: Discussionmentioning
confidence: 90%
“…In vasculature, they have recently been implicated in transducing the atherogenic effects of oscillatory shear stress (17) -one of the most well-studied examples of vascular mechanosensitivity (9). Additionally, YAP and TAZ are known to promote sprouting angiogenesis, even in systems that are not directly mechanically stimulated (24), through molecular regulators of sprout tip cell selection (53). In our studies, we observed a strong upregulation of YAP/TAZ target genes Cyr61 and Ctgf due to loading; this response was significantly abrogated by YAP/TAZ inhibitor VP only under the delayed loading condition.…”
Section: Discussionmentioning
confidence: 99%
“…When the promiscuous Gα protein is co-expressed with LPA 6 , LPA activates LPA 6 to increase intracellular Ca 2+ and reduce cAMP and ERK1/2 activation which stimulated by forskolin [9,47]. As already mentioned, the transcriptional regulators YAP and TAZ can be activated by the LPA-LPA 4 /LPA 6 -Gα12/Gα13 signaling pathway, and both YAP and TAZ are involved in tumor progression [35]. Moreover, another article mentions the binding of LPA to the LPA 6 receptor to regulate vascular permeability [49].…”
Section: Lpar6mentioning
confidence: 82%
“…It indicates that LPA4 receptor can promote angiogenesis and vascular development. In addition, the regulatory factor Yes-associated protein (YAP) and the transcriptional coactivator with PDZ-binding motif (TAZ) can also be activated by LPA4/LPA6 via the Gα12/Gα13 signaling pathway [35]. YAP and TAZ can accelerate the progression of cancer by promoting the proliferation and migration of cancer cells, such as accelerating liver cancer, bladder cancer and lung cancer [36][37][38].…”
Section: Lpar4mentioning
confidence: 99%